Simulation Based Study of Ground Mobile Robots for Inspection and Control of the Bridge Assembly Process - Pierluigi Rea; Erika Ottaviano; Lucia Figuli (Technologia i Automatyzacja Montażu)
Nowadays, the inspection of bridges poses a significant challenge for safeguarding critical infrastructures. Recent advancements have seen the integration of robots to replace human personnel in hazardous tasks. These robots, whether operating autonomously or through tele-operation, play a crucial role in monitoring structures and infrastructure, ensuring secure access to areas such as manholes on decks and box girder bridges. Specifically designed for environments deemed dangerous, difficult, or inaccessible to humans, ground mobilerobots equipped with appropriate sensors are increasingly deployed for inspection purposes.This paper addresses simulation tests conducted bya hybrid mobilerobot. Its compact design and maneuverability enable it to navigate through obstacles, making it suitable for inspecting railway or highway bridge decks as well as confined spaces within box girder bridges. The study includes a survey of existing bridges highlighting key issues to be addressed and presents simulation results for the hybrid rover. Automatic and robotic systems can play an important role for the control during the bridge assembling process increasingthe reliability of the structure andimprovingits operational propertiesand security.